Evidence of an abnormal epithelial barrier in active, untreated and corticosteroid‐treated eosinophilic esophagitis. Issue 1 (6th August 2017) - Simon, D.; Page, B.; Vogel, M.; Bussmann, C.; Blanchard, C.; Straumann, A.; Simon, H.‐U.
Abstract: Background: Eosinophilic esophagitis (EoE) is a chronic, immune/antigen‐mediated disease characterized by symptoms related to esophageal dysfunction and an eosinophil‐predominant inflammation. This study has aimed to investigate whether the recently observed sensitization to Candida albicans in patients with EoE is owing to pre‐existing disease and its underlying abnormal epithelial barrier or, alternatively, is linked to corticosteroid (CS) therapy. Methods: Medical histories, as well as serum and tissue samples of 60 patients with EoE (15 CS naive, 45 with current or previous CS therapy) and 20 controls, stored in the Swiss Eosinophilic Esophagitis Database (SEED) and Biobank, were analyzed. We applied ImmunoCAP to measure IgE levels and immunofluorescence techniques to examine epithelial barrier components. Results: Patients with EoE had higher total IgE levels and were more frequently sensitized to C. albicans than controls. In EoE tissue specimens, increased numbers of eosinophils and mast cells, a higher expression levels of thymic stromal lymphopoietin (TSLP), cathelicidin, proteases, that is, the kallikreins (KLK)‐5 and KLK‐7, were observed as compared with controls, while reduced expression of lympho‐epithelial Kazal‐type‐related inhibitor (LEKTI), filaggrin, E‐cadherin, claudin, occludin, desmoglein‐1 was found, independent of CS therapy. In CS‐treated EoE, significantly lower numbers of CD1a+ cells and cathelicidin expression were noted as compared to CS‐naive EoE. Conclusion: This study provides further evidence that EoE is associated with an abnormal epithelial barrier and postulates that CS therapy, by reducing innate immune mechanisms, may promote C. albicans colonization and likely subsequent sensitization.